Aptes Functionalization Of Cgnp Electrochemical Immunosensor For Detection Of Immunoglobulin G - Mohd Azraie Mohd Azmi; Fatihatul Zuriati Makmon; Nur Azura Mohd Said; Hazana Razali; Mohd Ifwat Mohd Ghazali; Shahino Mah Abdullah; Owen J Guy (Penerbitan UTHM, 2024)
Indexed by Scopus/ERA